Draft Annual Plan 1989-90 Volume I Government of Andhra Pradesh - Planning Commission (Planning Commission, 1988)
For the year 1988-89 the Planning Commission approved a plan of Rs 1250 crores and this was provided in the Vote-on- Account Budget. Subsequent to the Vote-on-Account Budget additional funds of Rs 171.75 lakhs were provided for Telugu Grameen Kranti Patham schemes and Rs 100.00 lakhs to the A.P.State Cooperative Rural Irrigation Corporation by taking advance from the Contingency Fund. Including those additional funds, the plan outlay for 1988-89 has been increased to Rs 1252.72 crores and this was included in the final budget.
Finance and Planning (Planning Wing) Department Government of Andhra Pradesh
Finance and Planning (Planning Wing) Department Government of Andhra Pradesh